Evaluation of Risk Management Implementation in IT Projects Using ISO 31000 in an ICT Solutions Company - Ranti Dwi Berlianti Bachtiar; Machmudin Eka Prasetya (Profesional Muda Cendekia Publishing, 2024)
Research Aims: This study aims to assess the implementation of risk management in information technology projects at PT. X, an ICT solutions company in Indonesia. Focusing on ISO 31000:2018 standards, the research aims to identify gaps in current risk management practices and prioritize potential risks for improved project planning. Design/methodology/approach: Utilizing a descriptive qualitative analysis with a case study approach, this research employs interview data collection and document analysis. The evaluation is centered on the adherence to ISO 31000:2018 standards in the risk management process at PT X and identification of eleven prioritized potential risks. Research Findings: The study reveals that the current risk management processes at PT X do not fully comply with ISO 31000:2018 standards. Additionally, eleven potential risks are identified, highlighting areas that require attention and improvement. The research emphasizes the importance of enhancing risk management practices for the company's sustainability. Theoretical Contribution/Originality: This research contributes by providing insights into the gaps in risk management practices within the context of information technology projects. It highlights the need for companies like PT X to align their risk management processes with international standards for improved project success. Research limitation and implication: Limitations include the focus on a specific company and the qualitative nature of the study. Future research may extend the analysis to multiple organizations and incorporate quantitative methods for a more comprehensive evaluation. The study recommends enhancing risk management aspects at PT X by implementing a project risk management policy, developing integrated risk management documents, and improving risk evaluation analysis. These improvements are crucial for the sustained success of information technology projects in the company.